The Geo-Demographic Dimension of Romanian Rural Space - Staşac, Marcu; Albu, Ioana; Stupariu, Marius (Bulletin of Geography. Socio-economic Series, 2010)
Knowing, researching into and developing the rural space are activities of utmost importance for a country, both by the dimension of the rural space, expressed by the surface as such, and by the dimension of the demographic component (of the rural population). Referring to Romanian rural space, this is dominant, representing almost 94% of Romania's total surface (93.7%). In what concerns the demographic component (population), as it is known, this confers a particular dynamics to the rural space, generating a series of quantitative and qualitative aspects. At present the share of the rural population reaches 47% out of the total of Romania's population. Generally speaking, we can assert that the village and generally the Romanian village remains further on the main propeller of life. Thus the share of the rural population, besides the whole range of socio-demographic indicators, which can outline the degree of stability or instability of the rural space, as well as other basic indicators, such as the share of the rural population occupied in productive activities, socio-cultural services, tourism activities, etc., enhance the importance of the rural life from one country or another, reason for which the development of the rural space remains a problem of a national and international level. Consequently, the Parliamentary Assembly of the Council of Europe has raised the issue of the rural space at the level of European and Community policy.